Republic of Croatia : First Review Under the Stand-By Arrangement and Requests for Waiver of Nonobservance of Performance Criteria and Rephasing of Purchases. (IMF Staff Country Reports; Country Report ;, 2005)
The staff report for the First Review Under the Stand-By Arrangement on the Republic of Croatia focuses on fiscal policy and monetary and financial sector policies. Financial soundness indicators show a continuation of the overall strengthening of the banking system, although foreign exchange-related credit risk remains high. Efforts to strengthen financial discipline in the broader public sector remain an important component of the program. Progress is continuing on the agenda of the original program in the areas of fiscal management and privatization.